Macro-Architectures in Spinal Cord Scaffold Implants Influence Regeneration - Wong, Darice Y. (Mary Ann Liebert, Inc., 2008)
Biomaterial scaffold architecture has not been investigated as a tunable source of influence on spinal cord regeneration. This study compared regeneration in a transected spinal cord within various designed-macro-architecture scaffolds to determine if these architectures alone could enhance regeneration. Three-dimensional (3-D) designs were created and molds were built on a 3-D printer. Salt-leached porous poly(ɛ-caprolactone) was cast in five different macro-architectures: cylinder, tube, channel, open-path with core, and open-path without core. The two open-path designs were created in this experiment to compare different supportive aspects of architecture provided by scaffolds and their influence on regeneration. Rats received T8 transections and implanted scaffolds for 1 and 3 months. Overall morphology and orientation of sections were characterized by H&E, luxol fast blue, and cresyl violet staining. Borders between intact gray matter and non-regenerated defect were observed from GFAP immunolabeling. Nerve fibers and regenerating axons were identified with Tuj-1 immunolabeling. The open-path designs allowed extension of myelinated fibers along the length of the defect both exterior to and inside the scaffolds and maintained their original defect length up to 3 months. In contrast, the cylinder, tube, and channel implants had a doubling of defect length from secondary damage and large scar and cyst formation with no neural tissue bridging. The open-path scaffold architectures enhanced spinal cord regeneration compared to the three other designs without the use of biological factors.